2021
DOI: 10.3390/cryst11121544
|View full text |Cite
|
Sign up to set email alerts
|

Modification of FA0.85MA0.15Pb(I0.85Br0.15)3 Films by NH2-POSS

Abstract: The surface composition and morphology of FA0.85MA0.15Pb(I0.85Br0.15)3 films fabricated by the spin-coating method with different concentrations of NH2-POSS were investigated with atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), angle-resolved X-ray photoelectron spectroscopy (AR-XPS), and Fourier transform infrared spectroscopy (FTIR). It was found that the surface composition of the FA0.85MA0.15Pb(I0.85Br0.15)3 films was changed regularly through the interaction between NH2-POSS and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…5b depict the possibility of elemental iodine or non-stoichiometric component formation after the cyclic test, indicating degradation of the undoped CuI semiconductor. 57,58 In contrast, EGTs with 20 mol% Br-doped CuI maintain the surface characteristics similar to as-coated films after the same consecutive scans (Fig. 4e).…”
Section: Resultsmentioning
confidence: 82%
“…5b depict the possibility of elemental iodine or non-stoichiometric component formation after the cyclic test, indicating degradation of the undoped CuI semiconductor. 57,58 In contrast, EGTs with 20 mol% Br-doped CuI maintain the surface characteristics similar to as-coated films after the same consecutive scans (Fig. 4e).…”
Section: Resultsmentioning
confidence: 82%
“…Materials 2023, 16, x FOR PEER REVIEW solar cells protected by the POSS passivation layer were also more stable and o degradation of the PCE in an inert atmosphere of N2 was noted after 1000 h (Figu As was already mentioned, the presence of POSS is beneficial, but its quan be optimized because the inorganic cube acts also as an insulator. It was shown surface composition of the FA0.85MA0.15Pb(I0.85Br0.15)3 films and their morphology in a regular manner in the presence of POSS−NH2 as a result of its interaction perovskite film [55]. When the amount of silsesquioxane exceeded the optimum tration (10 mg/mL), the quality of the perovskite film surface morphology was mised by the formation of cracks (Figure 8).…”
Section: Poss As a Moisture Barrier In Perovskite Filmsmentioning
confidence: 96%
“…As was already mentioned, the presence of POSS is beneficial, but its quantity must be optimized because the inorganic cube acts also as an insulator. It was shown that the surface composition of the FA 0.85 MA 0.15 Pb(I 0.85 Br 0.15 ) 3 films and their morphology changed in a regular manner in the presence of POSS-NH 2 as a result of its interaction with the perovskite film [55]. When the amount of silsesquioxane exceeded the optimum concentration (10 mg/mL), the quality of the perovskite film surface morphology was compromised by the formation of cracks (Figure 8).…”
Section: Poss As a Moisture Barrier In Perovskite Filmsmentioning
confidence: 99%